Walnut N-Acetylserotonin Methyltransferase Gene Family Genome-Wide Identification and Diverse Functions Characterization During Flower Bud Development - Ma, Kai; Xu, Ruiqiang; Zhao, Yu; Han, Liqun; Xu, Yuhui; Li, Lili; Wang, Juan; Li, Ning (Frontiers in Plant Science, 2022)
Melatonin widely mediates multiple developmental dynamics in plants as a vital growth stimulator, stress protector, and developmental regulator. N-acetylserotonin methyltransferase (ASMT) is the key enzyme that catalyzes the final step of melatonin biosynthesis in plants and plays an essential role in the plant melatonin regulatory network. Studies of ASMT have contributed to understanding the mechanism of melatonin biosynthesis in plants. However, AMST gene is currently uncharacterized in most plants. In this study, we characterized the JrASMT gene family using bioinformatics in a melatonin-rich plant, walnut. Phylogenetic, gene structure, conserved motifs, promoter elements, interacting proteins and miRNA analyses were also performed. The expansion and differentiation of the ASMT family occurred before the onset of the plant terrestrialization. ASMT genes were more differentiated in dicotyledonous plants. Forty-six ASMT genes were distributed in clusters on 10 chromosomes of walnut. Four JrASMT genes had homologous relationship both within walnut and between species. Cis-regulatory elements showed that JrASMT was mainly induced by light and hormones, and targeted cleavage of miRNA172 and miR399 may be an important pathway to suppress JrASMT expression. Transcriptome data showed that 13 JrASMT were differentially expressed at different periods of walnut bud development. WGCNA showed that JrASMT1/10/13/23 were coexpressed with genes regulating cell fate and epigenetic modifications during early physiological differentiation of walnut female flower buds. jrASMT12/28/37/40 were highly expressed during morphological differentiation of flower buds, associated with altered stress capacity of walnut flower buds, and predicted to be involved in the regulatory network of abscisic acid salicylic acid, and cytokinin in walnut. The qRT-PCR validated the results of differential expression analysis and further provided three JrASMT genes with different expression profiles in walnut flower bud development. Our study explored the evolutionary relationships of the plant ASMT gene family and the functional characteristics of walnut JrASMT. It provides a valuable perspective further to understand the complex melatonin mechanisms in plant developmental regulation.